2009
DOI: 10.1177/0146167209346170
|View full text |Cite
|
Sign up to set email alerts
|

Social Vigilantism: Measuring Individual Differences in Belief Superiority and Resistance to Persuasion

Abstract: Social vigilantism (SV) is an enduring individual difference that assesses the tendency of individuals to impress and propagate their "superior" beliefs onto others to correct others' more "ignorant" opinions. After establishing a reliable measure of SV, three studies showed that SV was associated with greater expressions of belief superiority (whether reacting to others holding dissimilar or similar beliefs) and greater resistance to persuasion (via increased rates of counterarguing and greater attitude stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 27 publications
1
44
0
2
Order By: Relevance
“…Maccoby (2000;see also DuBrin, 2012) theorized that narcissistic executives are poor listeners because they are distrustful of others' intentions. When individuals high on narcissism encounter others who have beliefs that are different from their own, they tend to think that those views are inferior and ignorant; they may even attempt to correct those views (Saucier & Webster, 2010). This is consistent with Smalley and Stake (1996; see also Morf & Rhodewalt, 1993) who found that when narcissists encounter feedback that conflicts with their grandiose sense of self, they tend to discredit the person who provided the feedback and disregard the feedback as being inaccurate.…”
Section: Consequences For Advice Takingsupporting
confidence: 58%
See 1 more Smart Citation
“…Maccoby (2000;see also DuBrin, 2012) theorized that narcissistic executives are poor listeners because they are distrustful of others' intentions. When individuals high on narcissism encounter others who have beliefs that are different from their own, they tend to think that those views are inferior and ignorant; they may even attempt to correct those views (Saucier & Webster, 2010). This is consistent with Smalley and Stake (1996; see also Morf & Rhodewalt, 1993) who found that when narcissists encounter feedback that conflicts with their grandiose sense of self, they tend to discredit the person who provided the feedback and disregard the feedback as being inaccurate.…”
Section: Consequences For Advice Takingsupporting
confidence: 58%
“…high on narcissism'' (p. 602). After all, narcissists tend to believe that their opinions are superior to others, and as a result, they exhibit resistance to persuasion (Saucier & Webster, 2010). Consistent with this, Collins and Stukas (2008) found that narcissism interacted with process accountability to predict self-presentational behavior.…”
Section: Self-enhancement and The Role Of Accountabilitymentioning
confidence: 70%
“…However, ideas have implications, and precipitate action (von Mises, 1963). Especially on "hot" topics-of a political, religious, or ethical nature-attitudinal disagreement is a diagnostic sign of realistic conflict, albeit latent rather than manifest.Furthermore, at a more fundamental level, beliefs can be considered the psychological equivalent of personal possessions (Abelson, 1986; Gregg, Mahadevan, & Sedikides, 2017a) SOCIAL STATUS AND IDEOLOGICAL OPPONENTS 7 which people wish to retain, or some occupied land which people which to expand (Saucier & Webster, 2010). That is, people relate psychologically to their beliefs partly as if they were physical objects or extended spaces: they can be mentally materialistic and ideologically territorial (Gregg & Mahadevan, 2014; Gregg, Mahadevan, & Sedikides, 2017b Gregg et al, 2017b).…”
mentioning
confidence: 99%
“…Some researchers have argued that personality traits such as "social vigilantism"-the tendency to impose one's own beliefs on others-predict greater expressions of belief superiority and increased counter-arguing tendencies (Saucier & Webster, 2010). Other researchers have expressed the somewhat contrasting view that motivated reasoning tendencies are linked to low self-esteem (Wiersema, van Harreveld, & van der Pligt, 2012), negative mood (Jonas, Graupmann, & Frey, 2006), and threats of social exclusion (Greitemeyer, Fischer, & Kastenmüller, 2012).…”
Section: Motivated Reasoning and Misinformation Effectsmentioning
confidence: 99%